Features of pharmaceutical marketing in retail trade ("Journal "U". Economy. Management. Finance.", 2025)
The article discusses the features of pharmacy retail that influence the formation of a successful business strategy. Pharmacy retail offers a wide range of products, including medicines, dietary supplements, cosmetics and personal care products. Each of these segments has its own characteristics, such as licensing, prescription regimen, and seasonal fluctuations in demand. Consumers in pharmacy retail often make decisions based on emotional and rational factors. In the article, the author conducted an analysis of the pharmacy business in the region, the results of which emphasize the need for constant market research and adaptation of marketing strategies in accordance with changes in consumer behavior and the competitive environment in order to achieve sustainable development in pharmacy retail.
Keywords: competitiveness; consumer behavior; advertising and promotion; assortment management